The Relationship of Self Esteem with the Aggressive Behavior of Class X Students of Mechanical Engineering Vocational High School 5 Padang - Tia Yunila Putri; Jarudin Jarudin; Rici Kardo (Universitas PGRI SUMATERA BARAT, 2023)
The background of this research is that there are students who have not been able to control themselves, students still violate school rules, students have not been able to master their own emotions and understand the emotions of others, resulting in fights/fights such as making fun of each other, berating each other, yelling, insulting and hitting, students who grumble at the teacher during lerning and when there are students who make mistakes, students like to kick chairs and tables during learning, students like to scribble on their hands, walls, tables, chairs and absence. Large aggressive behavior can also allow for a relationship between self-esteem and aggressive behavior. This study aims to describe 1) self-esteem of students, 2) aggressive behavior of students, 3) the relationship between self-esteem and aggressive behavior of students. This type of research is descriptive quantitative with a correlational approach. The data collection tool used is a questionnaire with the data analysis technique used is pearson product moment. The population of this study was students in class X mechanical engineering at vocational high school 5 Padang, totaling 65 students. The sampling technique was carried out using a total sampling, namely 65 students who became the research sample. The results of the research are recommended for counseling teachers and subject teachers to provide services and materials so that students can increase self-esteem from the medium to high category. So with high student self-esteem, student aggressive behavior will be low.